Studium interakcí telomerových proteinů za použití kvantitativních přístupů - Stojaspal, Martin (2015)
Telomeres are nucleoprotein structures at the ends of linear eukaryotic chromosomes. In mammals they are created by tandem repeats with 5´ - TTAGGG - 3´ sequence. Telomere protection is ensured by a protein complex called shelterin which consists of six proteins and protects the telomeres against DNA degradation, recombination or fusion between chromosomal ends. Shelterin proteins TRF1 and TIN2 are important for telomere cohesion during the cell cycle and as well, due to their interaction with SA1, a protein of cohesin complex, another protein complex which is necessary for chromosomal cohesion. Here we studied which domain or domains of SA1 and TRF1 are implicated in that interaction. Specifically, we cloned and expressed different truncated versions of TRF1. We performed fluorescence spectroscopy assays having as partners the TRF1 domains and the N-terminal domain of SA1, which is known that it is the interacting domain of this cohesin with the telomeric protein. After several measur